Penghentian Prematur Atas Prosedur Audit Pada Kantor Akuntan Publik (KAP) di Semarang - Nurdhiana, Nurdhiana; Adnanti, Wenny Ana; Kristiyani, Feby (Jurnal Ilmiah Aset, 2019)
The research was aimed to analyse the influence of time pressure, audit risk, materiality, review procedure and quality control, locus of control, self esteem in relation to ambition, turn over intention to premature sign-off of audit procedure. The population of this research were 243 auditors who worked at Public Accountant Firm in Semarang. While the samples of this research are 113 auditors. The technique sampling in this research is non probability sampling with purposive sampling method based of judgement sampling. The analysis technique used was multiple linear regression. The result of this research indicates that time pressure, locus of control, and turn over intention have positive significant influence on premature sign-off of audite procedure, but audit risk, materiality, review procedure and quality control, and self esteem in relation to ambition didn’t have influence on premature sign-off of audite procedure.